2003
DOI: 10.1073/pnas.1830978100
|View full text |Cite
|
Sign up to set email alerts
|

A causal role for endothelin-1 in the pathogenesis of osteoblastic bone metastases

Abstract: O steoblastic metastases occur in advanced cases of prostate cancer and frequently in breast cancer (1). Many factors have been proposed to cause disorganized new bone formation at sites of metastases, including insulin-like growth factors 1 and 2, transforming growth factor (TGF)-␤, prostate-specific antigen, urokinase-type plasminogen activator, fibroblast growth factors (FGF)-1 and -2, bone morphogenic proteins (BMPs), and, in particular, endothelin-1 (ET-1) (2-7).ET-1 is a potent vasoconstrictor that binds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
216
1
8

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 350 publications
(234 citation statements)
references
References 37 publications
9
216
1
8
Order By: Relevance
“…(16) Tumor-produced ET-1 may also have a major role in the establishment of osteoblastic bone metastases in prostate and breast cancer. (46,47) In the present study, the number of metastatic lung nodules in the mice treated with ABT-627 was significantly lower than that in the control mice in the experimental lung metastasis model (P = 0.001). ABT-627 clearly inhibits experimental lung metastasis in nude mice.…”
Section: Discussioncontrasting
confidence: 41%
“…(16) Tumor-produced ET-1 may also have a major role in the establishment of osteoblastic bone metastases in prostate and breast cancer. (46,47) In the present study, the number of metastatic lung nodules in the mice treated with ABT-627 was significantly lower than that in the control mice in the experimental lung metastasis model (P = 0.001). ABT-627 clearly inhibits experimental lung metastasis in nude mice.…”
Section: Discussioncontrasting
confidence: 41%
“…ET-1 mediates its effects on bone formation through the Endothelin A (ET A ) receptor. In a xenograft breast cancer model of osteoblastic bone metastasis, treatment with endothelin-1A-receptor antagonist reduced both osteoblastic bone metastases and tumor burden [32]. Osteoblastic prostate and breast cancers express ET-1 and ET A receptor, suggesting that tumor produced ET-1 may have paracrine and autocrine effects.…”
Section: Osteoblastic Bone Metastasismentioning
confidence: 95%
“…Animal models of breast cancer bone metastases show survival increases with agents that target bone responses to tumor, such as increased osteoclastic bone resorption with bisphosphonates (Daubiné et al 2007;Coleman 2009) or increased osteoblastic activity with endothelin receptor antagonists (Yin et al 2003;James et al 2009), rather than directly inhibiting tumor cells. Recent clinical trials have shown improved survival in breast (Coleman 2009) and prostate (James et al 2009) cancer patients, respectively, treated with these agents.…”
Section: Pathophysiology Of Bone Metastases: Role Of the Bone Microenmentioning
confidence: 99%